THE REPRESENTATION OF BEAUTY LANGUAGE IN TIKTOK’S K-BEAUTY CULTURE: A STUDY OF CULTURAL PRESSURE AND IDENTITY FORMATION - Rusida, Elizabeth (Jurnal Bahasa Asing, 2025)
This study investigates how beauty-related language on TikTok constructs and normalizes beauty ideals within K-beauty discourse. Focusing on recurring  expressions such as glass skin, flawless, and perfect V-shape face, the research aims to examine how linguistic repetition contributes to cultural pressure and digital identity formation among users. Using a qualitative approach, data were collected from selected TikTok videos and their comment sections and analyzed through Critical Discourse Analysis. The findings reveal that beauty language on TikTok functions as more than aesthetic description; it operates as a discursive mechanism that reinforces normative standards, emotional alignment, and algorithm-driven visibility. This study contributes to digital discourse research by highlighting the central role of language in shaping beauty ideology and identity performance within participatory social media environments.